QS4: A Quantitative Analysis Of The Upper Airway Volume In Patients With Attention Deficit Hyperactivity Disorder: A Cone-Beam Computed Tomography Study - ElNaghy, Rahma (Plast Reconstr Surg Glob Open, 2021)
PURPOSE: Attention deficit hyperactivity disorder (ADHD) is a developmental disorder affecting the quality of life. The etiology of ADHD is unclear, yet it has been believed to be multifactorial. he aim of this Cone-beam computed tomography (CBCT) study was to assess the upper airway morphology in adolescents with ADHD compared to controls. METHODS: A total of 454 patients who had CBCT taken as part of their initial orthodontic records were reviewed for eligibility. 87 subjects were included in the study. CBCTs volumes were utilized for three-dimensional evaluation of volumetric, minimum cross-section area and linear measurements of the upper airway in different planes. Two sample T-test and Man-Whitney U test were used to calculate and compare the mean values of the airway measurements between ADHD and control groups. RESULTS: There were significant differences in airway widths at planes A (p =0.002), C (p =0.042) and D (p <0.001), and in airway area at plane D (lower hypopharynx) (p <0.001), with the ADHD group showing narrower widths and area compared to controls. The mean overall airway volume in the ADHA group was smaller than in the control group but the difference was not significant. CONCLUSION: ADHD-affected adolescents have narrower upper airway dimensions compared to controls. Further investigations with larger samples are warranted to further elucidate the relationship between sleep-disordered breathing and ADHD.